Modern challenges and approaches to humanitarian engineering - Koumpouros, Yiannis; Georgoulas, Angelos, 1975-; Kremmyda, Georgia, 1979- (Advances in human services and public health book series., 2022)
"This book is those who want to improve their understanding of the strategic role of humanitarian engineering at different levels of the modern world and the various challenges facing our society, covering a wide variety of topics that fall under the domain of technology-based solutions that tackle humanitarian problems, such as pandemics, ageing of population, climate change, social inclusion, extreme poverty and hunger, maternal health and child mortality, and education for all"--